DETERMINAN KEJADIAN WASTING PADA BALITA USIA 6-59 BULAN - Sarimin, Dorce Sisfiani; Palaguna, Sriwati; Anwar, Seniwaty; Rahman, Nursyahraeni Madika; Riswanti, Riswanti (Ensiklopedia of Journal, 2024)
Abstract: Nutrition is a global health problem, with 45.4 million or 6.7% of children under five suffering from wasting or underweight. One of the factors closely related to wasting is infectious diseases such as diarrhea and exclusive breastfeeding history. The purpose of this study was to determine the relationship between formula feeding and bottle use with the incidence of diarrhea in toddlers. The type of research is quantitative with a case control design. The research was conducted in November-December 2022 in the Susunan Baru Health Center working area. The sample amounted to 88 respondents. The research instrument used a research questionnaire. The results showed there was a relationship between the frequency of diarrhea (p value: 0.003) and exclusive breastfeeding history (p value: 0.043). It is recommended that mothers who have toddlers pay attention to the nutritional intake given to toddlers, especially to toddlers born with low body weight. In addition, it is expected that mothers pay attention to nutritional intake in toddlers who experience diarrhea so that their nutrition is fulfilled.Keywords: Toddler, Diarrhea, Wasting.